Idiopathic Aplastic Anemia: An Update - Elena E. Solomou (Clinical Hematology International, 2019)
“Bone marrow failure” encompass all the conditions and syndromes in which there are qualitative or quantitative disorders of one or more lineages (erythroid, myelomonocytic, and/or megakaryocytic). A few years ago, the pathophysiology of these syndromes was completely unknown. Today we have better knowledge for these diseases, allowing the development of new treatment options and the improvement of patients' outcome. Acquired bone marrow failure syndromes include myelodysplastic syndromes, aplastic anemia, paroxysmal nocturnal hemoglobinuria, idiopathic neutropenia and large granular leukemia. All these syndromes share some common features and pathophysiology. The most important feature is the possibility of clonal evolution and progression into acute myelogenous leukemia, and open questions still remain on how to prevent evolution in these patients.